2020
DOI: 10.5688/ajpe7827
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intersession Course Remediation on NAPLEX/PCOA Scores in an Accelerated Doctor of Pharmacy Program

Abstract: Objective. To compare Pharmacy Curriculum Outcomes Assessment (PCOA) scaled scores and North American Pharmacist Licensure Examination (NAPLEX) pass rates in students who completed a twoweek intersession remediation or repeated a course with the scaled scores and pass rates of students who did not require any form of didactic remediation and did not have to repeat a course. Methods. Data examined for this study included NAPLEX/PCOA scores, NAPLEX pass/fail status, and remediation history for students at one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Palmer and colleagues most recently examined NAPLEX pass rates in students at an accelerated three-year program who completed remediation between quarters compared to students who did not require remediation and did not have to repeat a course. 4 Their analysis found lower NAPLEX performance for students who remediated or repeated multiple courses but no difference for students who remediated only one course. Although the timing of when remediation occurred varied, our analysis identified a similar association of the impact of a singular remediation versus multiple remediations on NAPLEX outcomes, suggesting that remediation as an intervention for single course deficiencies may be acceptable.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Palmer and colleagues most recently examined NAPLEX pass rates in students at an accelerated three-year program who completed remediation between quarters compared to students who did not require remediation and did not have to repeat a course. 4 Their analysis found lower NAPLEX performance for students who remediated or repeated multiple courses but no difference for students who remediated only one course. Although the timing of when remediation occurred varied, our analysis identified a similar association of the impact of a singular remediation versus multiple remediations on NAPLEX outcomes, suggesting that remediation as an intervention for single course deficiencies may be acceptable.…”
Section: Discussionmentioning
confidence: 95%
“…Two studies have demonstrated that students requiring remediation for deficient course grades have lower NAPLEX pass rates compared with those who did not require remediation; however, these studies did not investigate remediated course characteristics, such as the content area covered by the course, or which year in the program these remediations occurred. 3,4 These studies highlight the need for further validation and analysis of characteristics of remediation that may impact NAPLEX pass rates.…”
Section: Introductionmentioning
confidence: 99%